Efecto de tres fertilizantes orgánicos en el comportamiento agronómico del cultivo del fréjol (Phaseolus vulgaris L) en el Recinto Calope de Garrido Cantón Pangua Provincia de Cotopaxi - Campos Bajaña, Leonela Marian (2022)
The research project was carried out in the "paradise" farm belonging to the Canton Pangua, Recinto Calope de Garrido, province of Cotopaxi, with the general objective of evaluating the effect of three organic fertilizers on the agronomic behavior of the bean crop (Phaseolus vulgaris L. .) and as specific objectives to analyze the morphological development of the bean crop with the application of organic fertilizers, earthworm humus, bocashi and compost, to evaluate the performance of the application of organic fertilizers in the bean crop and to carry out the economic analysis of the treatments. in study. The research was carried out in a 168 m2 plot with a total of 20 plots and 500 plants, with a duration of 90 days from the implementation of the crop to the harvest. The variables evaluated were: plant height (cm), days to flowering, which was obtained when the crop reached 50% flowering, number of pods per plant, pod length (cm), number of grains per pod, days to harvest, yield (Kg) these last variables were taken when the harvest was carried out. A completely randomized block design (DBCA) was applied, with 25 experimental units, a design composed of five treatments and four repetitions, where five plants were evaluated for each experimental unit. In the plant height variable, the compost treatment obtained the best result with an average of 43.00 cm followed by earthworm humus and bocashi with 40.00 cm, while in the other variables the treatment that obtained the highest averages was the earthworm humus, with a yield of 2.50 kg/plot, positioning this fertilizer as the best in research. The highest benefit/cost ratio was obtained in the humus treatment with 0.63 USD followed by bocashi with 0.50 USD.